Minimally invasive search for a missing vibrator - Greg J. Marchand; Ali Azadi; Akarshi Kaue Brar; Katelyn Sainz; Sienna Anderson; Stacy Ruther; Kelly Ware; Sophia Hopewell; Giovanna Brazil; Katerina Meassick; Hannah Wolf; Alexa King; et al. (Korean Society of Obstetrics and Gynecology, 2020)
Objective To report a unique surgical procedure that was utilized to locate a missing vibrator in the pelvis of a patient. Emergency room admissions and surgery secondary to the malfunctioning of devices intended for sexual stimulation are extremely common. Emergency room staff of hospitals in the United States usually are skilled in the detection and removal of these devices. Occasionally, surgical intervention is warranted if the device enters a cavity that cannot safely be explored in the emergency room setting. We report a case of a vibrator that was lost during sexual activity. A flat plate X-ray showed it to be in the abdominal cavity. Careful questioning of the patient revealed that the device had an unusually small diameter. Surgical intervention showed that the device ultimately ended up in the bladder without causing traumatic injury. Methods We created a narrated video to demonstrate the surgical procedure (Canadian Task Force Classification III). Results Laparoscopy and cystoscopy were used to visualize and successfully remove the device. The patient recovered uneventfully. Conclusion Following laparoscopic confirmation of the location of the device, it was removed via cystoscopy. This case demonstrates how background information, such as the size of the missing device in this case, can be critical to providing high quality patient care.